SAT0362 ASSOCIATION OF GUT DYSBIOSIS WITH STRUCTURAL DAMAGE AND ACTIVITY IN AXIAL SPONDYLOARTHRITIS PATIENTS. DATA FROM THE COSPAR REGISTRY. (2nd June 2020) - Ignacio, G. G.; Moreno-Indias, I.; Castro Villegas, M. D. C.; Abalos-Aguilera, M. D. C.; Ladehesa Pineda, M.; Aranda-Valera, I. C.; Gutierrez Repiso, C.; Escudero Contreras, A.; Yolanda, J. G.; Barbarroja, N.; Tinahones, F. J.; Collantes Estevez, E.; et al.
Abstract : Background: The etiopathogenesis of axial spondyloarthritis (AxSpA) is multifactorial. The possible role of alteration in gut microbiome (dysbiosis) has been recently suggested. However, the association of dysbiosis with structural damage is still unknown and further studies are needed to assess its association with disease activity. Objectives: To determine the alterations in the gut microbiota in AxSpA patients. To evaluate whether changes in the gut microbiota in AxSpA patients are associated with structural damage or disease activity. Methods: Fifteen AxSpA patients and 15 healthy donors (HDs) were included in a cross-sectional study. Disease activity variables such as C-reactive protein and ESR were measured. Structural damage was determined by lateral X-rays of the cervical and lumbar spine to establish the mSASSS index. Axial mobility was evaluated using the BASMI index and the enthesis affectation was evaluated using ultrasound to obtain the MASEI index. Gut microbiota was measured using the Ion Torrent S5 platform and sequences were processed using the QIIME2. Chi-square and Mann-Whitney U were used, and correlations were determined using the Spearman Rho test. Significant differences were considered p <0.05. Results: Alpha diversity indicators, such as the number of observed OTUs group and the faith index, showed a greater richness in AxSpA compared to HDs (p=0.03 and p=0.01). A significant decrease in family Bacteroidaceae (p=0.006) and an increase in families Synergistaceae and Bifidobacteriaceae were found in the microbiota of AxSpA (p=0.036, p=0.049). According to genera, Bacteroides decreased in AxSpA (p=0.006), while Dialister and Bifidobacterium increased (p=0.010 and p=0.046). Positive correlation among lumbar mSASSS (r=0.508, p=0.019) and Synergistaceae was found. This family was also increased along with the increase in enthesis damage (MASEI index (r=0.656, p=0.028)) and axial mobility by the BASMI index (r=0.529, p=0.011). Correlation studies between the decrease in Bacteroidaceae and Bacteroides with disease activity measured by ASDAS (r=-0.697, p=0.025; r=-0.770, p=0.009) was also significant. Positive correlation was observed between Dialister with mSASSS (r=0.549, p=0.010) and BASMI (r=0.512, p=0.015). Conclusion: 1) AxSpA patients had a significant alteration of the gut microbiota. 2) These alterations are associated with radiographic damage, disease activity, affectation of enthesis and axial mobility. Acknowledgments: PRL, supported by "Sara Borrell" (CD19/00216), IMI supported by "Miguel Servet tipo I" (CP16/00163), CGR supported by JdC Incorporación (IJCI-2017-33065). This work is supported by JA PI-0151-2018. Pablo Rodríguez Bada metagenomic platform CIBER-IBIMA. Disclosure of Interests: Gómez García Ignacio: None declared, Isabel Moreno-Indias: None declared, María del Carmen Castro Villegas: None declared, Maria del Carmen Abalos-Aguilera: None declared, MLourdes Ladehesa Pineda: None declared, Inmaculada Concepcion Aranda-Valera: None declared, Carolina Gutierrez Repiso: None declared, Alejandro Escudero Contreras Grant/research support from: ROCHE and Pfizer, Speakers bureau: ROCHE, Lilly, Bristol and Celgene., Jiménez Gómez Yolanda: None declared, Nuria Barbarroja: None declared, Francisco Jose Tinahones: None declared, Eduardo Collantes Estevez Grant/research support from: ROCHE and Pfizer, Speakers bureau: ROCHE, Lilly, Bristol and Celgene, Patricia Ruiz-Limon: None declared